From ‘Little Things’ to ‘Seagulls’: A Mixed Methods Exploration of Patients' Experiences of Person‐Centred Compassionate Care in General Medical and Surgical Wards - Ruth Cox; Jayne Hewitt; Emilia Dauway; Alex McConnell; Jodie Nixon; Faiza El‐Higzi; Sanjeev Naidu; Elizabeth Ward (Health Expectations, 2026)
ABSTRACT Background Person‐centred compassionate care (PCCC) shapes the quality of relationships between health care professionals (HCPs) and patients, influences how healthcare is experienced, and ultimately can impact patient outcomes and HCP satisfaction. There is limited evidence about patient perspectives of multidisciplinary PCCC in acute general medical and surgical wards. Objective This study aimed to explore patients' perceptions of PCCC to inform co‐design of an intervention to enhance PCCC in general medical and surgical wards. Methods Sixty (60) inpatients on a general medical or general surgical ward completed the Sinclair Compassion Questionnaire (SCQ) three times—considering their interactions with doctors, nurses, and allied health separately. They also completed five qualitative questions about PCCC. An additional 20 patients or their carers were interviewed exploring the same five topic areas. Reflexive thematic analysis was used to analyse qualitative data. Results The median SCQ score was high (4.5; SEM = 0.05) indicating that participants perceived high levels of compassion from HCPs during their hospital admission. Fewer than 20 per cent (17.9%) of the SCQ scores were less than 4 out of 5 and more than half (51.2%) were 4.5 or higher. Analysis revealed no significant differences ( p = 0.066) between professional groups (Doctors: median = 4.2, SEM = 0.10; Nurses: median = 4.75, SEM = 0.07; Allied Health: median = 4.25, SEM = 0.09). There were no significant differences in scores ( p > 0.01) by ward type, length of stay, cultural diversity, or disability. Females rated allied health staff as significantly higher on SCQ (median = 4.9, SEM = 0.1) than males (median = 4, SEM = 0.15) ( p = 0.003). Qualitative responses indicated many recommendations to enhance care. From ‘little things’ to ‘seagulls’ was a phrase co‐created by the research team to encapsulate the range of participant perspectives across the themes. Co‐produced themes and key messages to staff focussed on being in the moment, finding out about the whole patient and their journey, partnering with the patient to the level they choose, knowing that patients make allowances for the pressures on staff, and that small acts of kindness are critical to the patient experience. Conclusion This co‐produced research privileged the voice of a diverse group of patients and provided new and actionable insights regarding PCCC across HCPs in acute hospital general medical and general surgical wards. Findings emphasised that SCQ scoring was a useful ‘temperature check’ regarding PCCC indicating that some improvements were needed. However, there may be a ceiling effect for the tool which requires further research. Qualitative data indicated where improvements were needed.